Osteoconductive scaffolds obtained by means of in situ surface functionalization of wet-spun fibre meshes for bone regeneration applications - Rodrigues, M. T. (2008)
[Excerpt] The success of bone tissue engineering (TE) strategies is strongly dependent on the development of new synthetic materials combining osteoconductive, osteoinductive and osteogenic properties. Recent studies suggest that biomaterials incorporating silanol groups promote and maintain osteogenesis with or without biological stimuli. This study aims to evaluate the osteoconductivity and osteogenic properties of novel wet-spun fibre mesh scaffolds of SPCL (blend of starch with polycaprolactone) with or without superficial functionalized silanol (Si-OH) groups by seeding/culturing them with goat marrow stromal cells (GBMCs). A calcium silicate solution was used as a non-solvent to precipitate the SPCL solution by wet-spinning and to develop an in situ functionalization methodology of the SPCL fiber mesh with silanol groups. [...]